The Influence of Teacher Welfare Perception and Self-Efficacy on Interest in Becoming a Teacher among Culinary Arts Education Students - Hamidah, Dina; Mariani, Mariani; Febriana, Rina (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study was to determine the effect of perceptions of teacher welfare and self-efficacy on the interest in becoming a teacher among students in the Culinary Education at Universitas Negeri Jakarta. This research was motivated by the low interest of students from education program in pursuing a career as a teacher. The research employed a quantitative approach with a survey method. The population consisted of active culinary education students from the 2020 and 2021 cohorts. The sampling technique used was purposive random sampling, referring to the Isaac and Michael table with a 5% margin of error, resulting in a sample of 84 students. Data were collected through a questionnaire using a Likert scale. The data analysis technique used was multiple linear regression, processed using SPSS version 25. The results of the F-test show that the calculated F-value 36.980 > F-table value 3.11, with a significance level of 0.000 < 0.05, indicating a significant simultaneous influence. The t-test results show that the teacher welfare perception variable (X1) had a t-value of 3.898 > t-table 1.993, and the self-efficacy variable (X2) had a t-value of 5.367 > t-table 1.993, with each variable having a significance value of 0.000 < 0.05, indicating a significant partial influence. Based on these results, it can be concluded that both simultaneously and partially, teacher welfare perception and self-efficacy significantly influence students’ interest in becoming teachers. The coefficient of determination of 0.477 indicates that 47.7% of the interest in becoming a teacher is influenced by these two variables, while the remaining 52.3% is influenced by other factors outside this study.